2015
DOI: 10.1002/srin.201400576
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Microstructure Evolution with Dynamic Recrystallization in Finite Element Simulations of Martensitic Steel

Abstract: A metallurgical material description of the flow behavior for finite element (FE) simulations was developed. During hot compression tests, the dynamic microstructure evolution is modeled on the example of high‐strength martensitic steel MS‐W 1200. Compression tests at 900–1000 °C with a strain rate of 0.1 s−1 on fine‐grain and coarse‐grain samples were performed. An analysis of the flow behavior identified a strong correlation between the dynamic recrystallization kinetics and the initial microstructure. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Investigations of rolling parameter using finite element method were performed by Ding et al and it was found that rolling temperature has a more significant effect on dynamic recrystallization than rolling speed. Baron et al used a regression analysis method to determine the parameters of the dynamic recrystallization model and incorporated it into a finite element model to simulate the hot compression of high strength martensitic steel. These literatures provide valuable background for the modeling and simulation of DRX during steel bar hot rolling process in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of rolling parameter using finite element method were performed by Ding et al and it was found that rolling temperature has a more significant effect on dynamic recrystallization than rolling speed. Baron et al used a regression analysis method to determine the parameters of the dynamic recrystallization model and incorporated it into a finite element model to simulate the hot compression of high strength martensitic steel. These literatures provide valuable background for the modeling and simulation of DRX during steel bar hot rolling process in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Initial austenite grain size was measured by microscopic analysis after quenching and an annealing treatment at T anneal = 823 K for 900 s. Resulting microstructure analysis shown in Fig. 2 lead to an average grain diameter of ݀ ̅ = 35 µm [10]. …”
Section: Methodsmentioning
confidence: 99%
“…Despite such wide applicability, DT has not yet developed into a practical tool for microstructural control. This contrasts with the accompanying process of dynamic recrystallisation (DRX), which is routinely incorporated in hot working simulations and optimisation efforts [6,7]. Unlike DRX, the fundamental and technological aspects of DT are still being resolved [2,3,5].…”
Section: Introductionmentioning
confidence: 99%